THE CORRELATION BETWEEN STUDENTS’ VOCABULARY AND GRAMMAR MASTERY IN THEIR PARAGRAPH WRITING ABILITY AT THE SECOND SEMESTER OF THE EIGHTH CLASS AT SMP NEGERI 8 BANDAR LAMPUNG - Zulianti, Hajjah; Gunawan, Gede (Lentera: Jurnal Ilmiah Kependidikan, 2014)
The objectives of this research are to know the correlation between students’ vocabulary mastery and grammar mastery, the correlation between students’ vocabulary mastery and their paragraph writing ability, the correlation between students’ grammar mastery and their paragraph writing ability, and the correlation between students’ vocabulary mastery and grammar mastery in their paragraph writing ability.In taking the sample of the research, the writer used Cluster Random Sampling Technique because the population is homogeneous.The population of the research was 334 students which consis of 9 classes. It was taken from the students of the second semester of the eighth class at Junior High School 8 of Bandar Lampung in 2012/2013. In collecting the data, the writer used an objective test that is multiple choice, consisted of 50 items for vocabulary and 40 items for grammar test, while for the writing the students were asked to make a composition based on the topic given. To analyze the data of the research the writer used multiple correlation.The result of the research showed that r-count = 0.8 is higher than r-table = 0.312. It means that there is a significant multiple correlation between students’ vocabulary and grammar mastery in their paragraph writing ability. So, the hypothesis is accepted.